New Diet Quality Index for children and adolescents in Costa Rica - Núñez Rivas, Hilda Patricia (2020)
Introduction: There is an increasing interest in the study of indicators of the quality of the total diet through the study of food groups of certain dietary patterns. Objective: Analyze the diet of students of Costa Rica with the construction of a contextualized and new diet quality index. Methods: A cross-sectional study was performed with a population of 2677 students of 64 educative centers. Their data on habits and food intake frequency were collected through interviews and questionnaires. A new Diet Quality Index was constructed and applied, which assessed the adjustment of the intake frequency of 22 food groups corrected with five preventive dietary factors and five risk factors for chronic non-communicable diseases. Descriptive statistics were performed with the program SPSS, version 24.0. A value of p ˂0.05 was considered significant. Results: The population was made up of 1259 (43%) men and 1418 women (57%). According to the new Diet Quality Index-Costa Rica classification, 1.2% (n = 33) of the participants have a healthy diet; 9.0% (n = 239) requires changes and 89.8% (n = 2 395) have an unhealthy diet; because of the excessive intake of processed foods (rich in sodium and fat) and the low consumption of fruits and vegetables. Significant differences were found in the averages of the Diet Quality Index-Costa Rica by sex, educational level and socioeconomic classes. Conclusions: Around 90% of the studied population are not complying with the recommendations to have a healthy diet. Nutrition education should be strengthened in Costa Rican education centers.